(untitled) (Nigerian Journal of Technology, 2019)
Chemical, mineralogical and petrological characterization of Gyaza iron ore deposit, Katsina State, Nigeria was carried out. The ore sample was sourced from Gyaza village, Kankiya Local Government Areas of Katsina State and comminuted using laboratory jaw crusher and pulverizing machines respectively. The comminuted sample was analyzed using XRF, XRD, SEM and OPM. The XRF result revealed that the ore contained 0.17%P, 0.02%K, 0.23%Ca, 0.11%Mn, 36.17%Fe, 0.08%Ba, 0.18%Mg, 1.10%Al and 17.21%Si. The XRD result revealed that the complex mineral phases of the ore are Aluminum-Silicate-Hydroxide-Hydrate (Al2Si2O5(OH)4.2H2O), Chrysotile (Mg3[Si2-xO5](OH)4-4x), Magnesium-Aluminum-Silicate-Hydroxide-Hydrate ((Mg,Al)9 (Si,Al)8O20 (OH)10.4H2O), Sodium-Calcium-Magnesium-Aluminum-Silicate (NaCa2Mg5AlSi7O22(OH)2), Sodium-Iron-Silicate-hydroxide ((Na,Ca) 2 (Fe,Mn)Fe2 (Si,Al)8O22 (OH)), Orthoclase (KAlSi3O8) and Sodium-Calcium-Iron-Aluminum-Silicate-Hydrate (NaCa2Fe4AlSi6Al2O22(OH)2). And the single mineral phases are Quartz (SiO2), Hematite (Fe2O3) and Goethite (Fe2O3.H2O) which are also the major minerals phases. The SEM and petrological results revealed that the ore matrix is an assemblage of inter-layered different minerals crystals with different shapes, sizes and angles of orientations and separated by grain boundaries. http://dx.doi.org/10.4314/njt.v38i3.17